Four new species of Aleiodes (Hymenoptera: Braconidae: Rogadinae) from the Neotropical Region - Garro, Lidia Sulca (2017)
Four new species of the Aleiodes apicalis (Brulle) species group (Hymenoptera: Braconidae: Rogadinae) from the Neotropical Region are described and illustrated: Aleiodes ambrosiae new species. from Peru, A. aquilesi new species from Costa Rica, and A. sachambrosiae new species and A. tapirape new species from Brazil. We also add new distribution records for Aleiodes molestus Cresson, from Costa Rica. With the addition of the new species, the A. apicalis species group has 11 species from the New World, six of which are recorded from Neotropical Region.